Optimization of Photocatalytic Degradation of Palm Oil Mill Effluent in UV/ZnO system based on Response Surface Methodology - Ng, Kim Hoong; Cheng, Yoke Wang; Khan, Maksudur R.; Cheng, C. K. (Elsevier Ltd, 2016)
This paper reports on the optimization of palm oil mill effluent (POME) degradation in a UV-activated-ZnO system based on central composite design (CCD) in response surface methodology (RSM). Three potential factors, viz. O2 flowrate (A), ZnO loading (B) and initial concentration of POME (C) were evaluated for the significance analysis using a 23 full factorial design before the optimization process. It is found that all the three main factors were significant, with contributions of 58.27% (A), 15.96% (B) and 13.85% (C), respectively, to the POME degradation. In addition, the interactions between the factors AB, AC and BC also have contributed 4.02%, 3.12% and 1.01% to the POME degradation. Subsequently, all the three factors were subjected to statistical central composite design (CCD) analysis. Quadratic models were developed and rigorously checked. A 3D-response surface was subsequently generated. Two successive validation experiments were carried out and the degradation achieved were 55.25 and 55.33%, contrasted with 52.45% for predicted degradation value.